1998
DOI: 10.1159/000024595
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Airborne Bacteria and Fungi in Bayside Offices in Rio de Janeiro, Brazil

Abstract: This paper provides the first published information on indoor concentrations of micro-organisms in a building in Rio de Janeiro, Brazil. The building in question was a 1,000 m2, twenty-nine-story building with a central air conditioning system. Concentrations and genera of bacteria and fungi were determined in several offices using a 6-stage impactor (Andersen sampler) during the summer season. Several gram-positive (Micrococcus, Bacillus, Staphylococcus, Streptococcus) and gram-negative (Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Exposures to species of Penicilium and Aspergillus sp have been associated with occupational asthma and hypersensitive pneumonitis. 9 However, the levels that were detected for airborne fungi in this study (Table 1) are lower than the recommended by Brazilian guidelines (750 cfu m -3 ).…”
Section: Airborne Fungicontrasting
confidence: 65%
See 1 more Smart Citation
“…Exposures to species of Penicilium and Aspergillus sp have been associated with occupational asthma and hypersensitive pneumonitis. 9 However, the levels that were detected for airborne fungi in this study (Table 1) are lower than the recommended by Brazilian guidelines (750 cfu m -3 ).…”
Section: Airborne Fungicontrasting
confidence: 65%
“…In the last decade, some researchers have been studying indoor air quality in Brazil, with the objective of improving the quality of people's lives and of determining what kinds of pollutants are commonly present. Studies evaluating air quality in offices, [8][9][10] dwellings 11 and printing facility 12 were performed in our laboratory. Most of these studies were developed in indoor environments where the occupants complained about health problems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Brickus et al 25 found that the microbiological concentration in the indoor air was similar to the outdoor values, which means that the I/O concentration ratio was close to 1. 25 However, by comparing obtained average values of I/O ratios with that proposed by Neto and Siqueira 26 (I/O 1.5 ¼ good; I/O ¼ 1.5-2.0 ¼ regular; I/O > 2 ¼ poor indoor conditions), the indoor conditions among cases can be considered to be relatively poor when compared to a regular indoor conditions among controls. A similar study by Roos et al 27 corroborated the fact that the most probable source of air contamination by microorganisms was indoor sources.…”
Section: Discussionmentioning
confidence: 87%
“…A range of instrumentation is available for monitoring moulds in the environment. These may be used for continuous measurement [36] or to sample air using viable cascade impactors based on the Anderson design [37] or related techniques [38]. The choice of sampler requires careful consideration of the purposes of the investigation, the information required, the characteristics of the moulds in the environment being studied and the sampling and trapping efficiencies of the available samplers.…”
Section: Monitoring and Risk Assessmentmentioning
confidence: 99%